2015
DOI: 10.1175/jcli-d-14-00201.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of Global Precipitation Change and Variability during 1901–2010

Abstract: This study examines global precipitation changes/variations during 1901–2010 by using the long-record GPCC land precipitation analysis, the NOAA/Cooperative Institute for Climate and Satellites (CICS) reconstructed (RECONS) precipitation analysis, and the CMIP5 outputs. In particular, spatial features of long-term precipitation changes and trends and decadal/interdecadal precipitation variations are explored by focusing on the effects of various physical mechanisms such as the anthropogenic greenhouse gas (GHG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 73 publications
4
51
2
Order By: Relevance
“…However, spatial distribution of temporal trends in the current study is more or less identical to the pattern resulting from the NASA GISS Climate Model E which detected significant decreasing trends in the south, south-west, north-west and north-east. Stronger trends detected in the current study (mostly between À3.1 and À 9.3 mm yr À1 ) are the result of using a more recent period (1987-2016) compared with 1979-2012 in Gu and Adler (2015) and 1951in Raziei et al (2014.…”
Section: Precipitationcontrasting
confidence: 42%
See 1 more Smart Citation
“…However, spatial distribution of temporal trends in the current study is more or less identical to the pattern resulting from the NASA GISS Climate Model E which detected significant decreasing trends in the south, south-west, north-west and north-east. Stronger trends detected in the current study (mostly between À3.1 and À 9.3 mm yr À1 ) are the result of using a more recent period (1987-2016) compared with 1979-2012 in Gu and Adler (2015) and 1951in Raziei et al (2014.…”
Section: Precipitationcontrasting
confidence: 42%
“…Iran is among those countries that have experienced the strongest linear trends in surface temperature during 1979-2012(Gu and Adler, 2015. Based on GISS global surface temperature anomalies, all over the country, except the south-east corner, revealed increasing trends in surface temperature of magnitudes >0.04°C yr À1 over the period 1979-2012.…”
Section: Temperaturementioning
confidence: 99%
“…For 1901–2013, a weak increasing linear trend [0.66 mm (10 years) −1 ] of the annual precipitation over Central Asia is consistent with the increase in the Northern Hemisphere mid‐ to high‐latitude lands by GPCC V6 and model simulations (Gu and Adler, ), and in global land (New et al ., ). The significant negative correlation (CC = −0.27) between Central Asia and global land can be explained by the opposite interdecadal variations compared with the global land precipitation (Nickl et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the long‐term precipitation data sets, previous studies revealed that the global land area has experienced an overall increasing trend in precipitation during the past century (Diaz et al ., ; Vinnikov et al ., ; Dai et al ., ; Hartmann et al ., ; Gu and Adler, ). However, precipitation changes show strong regional differences during the past century (Dai et al ., ; Wang et al ., ; Trenberth et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The Interdecadal Pacific Oscillation (IPO; Power et al, ), or its North Pacific counterpart—the Pacific Decadal Oscillation (Mantua et al, ), is the leading mode of sea surface temperature (SST) variability on decadal to multidecadal time scales in the Pacific basin that broadly resembles El Niño‐Southern Oscillation (ENSO)‐related SST anomaly patterns (Zhang et al, ). The IPO impacts surface temperature and precipitation over many parts of the world (e.g., Dai, ; Dong & Dai, ; Gu & Adler, ) and causes decadal changes in global warming rates (Fyfe et al, ). In particular, the cooling in the eastern Pacific since around 1993 associated with the IPO phase changes is likely a major cause for the recent slowdown in the global surface warming rate since the late 1990s (Dai et al, ; Kosaka & Xie, ).…”
Section: Introductionmentioning
confidence: 99%